Automatic, simultaneous control of polymer composition and molecular weight during free radical copolymer synthesis. (31st January 2018) - McAfee, Terry; Montgomery, Rick D.; Zekoski, Thomas; Wu, Aide; Reed, Wayne F.
Abstract: Fully automatic, simultaneous control of polymer composition and molecular weight trajectories during free radical copolymer synthesis was achieved by coupling the continuous ACOMP data stream into a feedback controller which operated pumps for reactor feed of comonomers. The controller operates without recourse to a detailed kinetic model or reactivity ratios. Rather, it uses the fact that instantaneous copolymer chain composition is related to the instantaneous rate of consumption of comonomers, and the rate for each of these is described by rates α1 and α2 for comonomers 1 and 2, respectively. The instantaneous weight average molecular weight Mw, inst is proportional to total comonomer concentration via a constant p. Hence, target trajectories for composition and Mw can be independently prescribed and followed. Since α1, α2 and p are directly measurable from the ACOMP data stream, their values can be constantly updated by the automatic controller during the reaction process to insure the target trajectories are followed. Graphical abstract: Highlights: First time fully automatic control of composition in free radical copolymerization. First time simultaneous fully automatic control of composition and molecular weight in free radical copolymerization. Combined composition and molecular weight controller uses only three directly measurable parameters and requires no detailed kinetic models. Various composition and molecular weight trajectories are used to illustrate power of the new capability.